Pengaruh Struktur Modal dan Profitabilitas terhadap Nilai Perusahaan - Putra, Andika Setiadiana; Veronica, Sienly (SAFE-Network, 2025)
Companies listed on the IDX in the infrastructure, utilities, and transportation subsector between 2018 and 2023 will be the focus of this study, which seeks to assess the impact of capital structure and profitability on firm value. This study uses a causal-comparative design and quantitative methodology to provide an explanation. Companies listed on the IDX in the infrastructure, utilities, and transportation subsector are the population in this study. Purposive sampling was used to select 27 companies that met certain criteria for the research sample. Annual financial reports served as a secondary data source. Using SPSS version 26, we conducted multiple linear regression analysis on the collected data. The significance threshold (α) used for hypothesis testing was 5% or 0.05. Firm value, as assessed by PBV, is positively and significantly affected by capital structure, as indicated by DER. A firm's value is positively and significantly affected by its profitability, as indicated by ROA. That is why investors value companies with a healthy financial structure and strong profitability more. Based on the findings of this study, organizations can increase their value and attractiveness to investors by optimizing capital structure and increasing profitability.